Maternal understanding and practices of breastfeeding and infant feeding in rural North Karnataka: a cross sectional study - Mallesh, Vidya; Patil, Shailaja S.; Sorganvi, Vijaya (International Journal Of Community Medicine And Public Health, 2023)
Background: Child-malnutrition is a critical global concern supported by substantial evidence. Recognizing optimal infant and young child-feeding practices as pivotal in combating malnutrition is crucial. Methods: This was a cross-sectional study conducted through house-to-house survey in Ukkali and Shivanagi villages for period of 6 months from February 2018 to July 2018. A pretested-questionnaire was administered to 133mothers of 6 to 12-month-old children, collecting socio-demographic data, knowledge, attitudes, and practices regarding prelacteal, breastfeeding, and complementary-feeding. Results: Knowledge gaps emerged, with only 50% understanding colostrum's importance. Limited awareness of exclusive breastfeeding (65%) and extended breastfeeding (31.57%) was observed. Prelacteal-feeding was widespread (52.63%), with sugar-water being a prevalent choice (21.8%). Most mothers (over 90%) opted for breastfeeding, yet timely initiation (27.6%) and exclusive-breastfeeding (30%) were suboptimal. Complementary-feeding initiation (15%) and minimum-meal-frequency adherence (13.3%) were low. Meal-diversity was deficient in over 60%. Conclusions: Bridging knowledge gaps and promoting optimal-feeding-practices through targeted nutritional education is essential. This study underscores the importance of addressing misconceptions, enhancing early-breastfeeding, and ensuring proper complementary-feeding to improve child-health outcomes. Socio-demographic-factors must be considered when designing educational material and interventions in rural-settings.